Sediment and nutrient storage in a beaver engineered wetland. Issue 11 (16th May 2018) - Puttock, Alan; Graham, Hugh A.; Carless, Donna; Brazier, Richard E.
Abstract: Beavers, primarily through the building of dams, can deliver significant geomorphic modifications and result in changes to nutrient and sediment fluxes. Research is required to understand the implications and possible benefits of widespread beaver reintroduction across Europe. This study surveyed sediment depth, extent and carbon/nitrogen content in a sequence of beaver pond and dam structures in South West England, where a pair of Eurasian beavers ( Castor fiber ) were introduced to a controlled 1.8 ha site in 2011. Results showed that the 13 beaver ponds subsequently created hold a total of 101.53 ± 16.24 t of sediment, equating to a normalised average of 71.40 ± 39.65 kg m 2 . The ponds also hold 15.90 ± 2.50 t of carbon and 0.91 ± 0.15 t of nitrogen within the accumulated pond sediment. The size of beaver pond appeared to be the main control over sediment storage, with larger ponds holding a greater mass of sediment per unit area. Furthermore, position within the site appeared to play a role with the upper‐middle ponds, nearest to the intensively‐farmed headwaters of the catchment, holding a greater amount of sediment. Carbon and nitrogen concentrations in ponds showed no clear trends, but were significantly higher than in stream bed sediment upstream of the site. We estimate that >70% of sediment in the ponds is sourced from the intensively managed grassland catchment upstream, with the remainder from in situ redistribution by beaver activity. While further research is required into the long‐term storage and nutrient cycling within beaver ponds, results indicate that beaver ponds may help to mitigate the negative off‐site impacts of accelerated soil erosion and diffuse pollution from agriculturally dominated landscapes such as the intensively managed grassland in this study. © 2018 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd. Abstract : Beavers, primarily through the building of dams, can deliver significant geomorphic modifications. This study surveyed sediment depth, extent and carbon/nitrogen content in a sequence of beaver pond and dam structures in South West England, where a pair of beavers were introduced in 2011. Results showed that the 13 beaver ponds, hold a total of 101.53 ± 16.24 t of sediment. The ponds also hold 15.90 ± 2.50 t of carbon and 0.91 ± 0.15 t of nitrogen.